Identification of Drug Related Problems (DRPs) Use of Antibiotics in Pediatric Pneumonia Patients at General Hospital Bengkulu City - Mahardika, Halwa Balqis; Dian Handayani; Rahmawati, Reza; Yudha, Sal Prima (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Pneumonia in pediatrics has a high mortality rate. Primary antibiotic therapy can increase antibiotic use and cause Drug Related Problems (DRPs). This study examines the treatment profile and identifies DRPs of antibiotic use in pediatric pneumonia patients at Ummi General Hospital, Bengkulu City. This study uses a cross-sectional approach method where data is collected retrospectively through patient medical records. The population includes all pediatric patients with the main disease community-acquired-pneumonia who were treated at the Ummi General Hospital, Bengkulu City during the July-December 2022 period. The sampling technique in this study was using purposive sampling. Data was analyzed univariately, and DRPs were identified using the Pharmaceutical Care Network Europe Foundation (PCNE) algorithm version 9.1 and analyzed descriptively. The treatment profile included ampicillin inj + gentamicin inj (54.7%), sultamicillin inj (15.8%), sultamicillin inj + gentamicin inj (8.4%), ampicillin inj (8.4%), gentamicin inj (7.4%), ceftriaxone inj (3.2%), and sultamicillin inj + gentamicin inj + ceftriaxone inj (2.1%). There were 367 cases in 95 patients. Cases of DRPs included overdose (27.8%), the duration of treatment is too short (22.9%), infrequent dose regimen (18.8%), adverse drug incidence (16.9%), underdose (10.1%), drugs not following the guidelines (1.9%), the duration of treatment is too long (1.1%), and therapeutic group duplication (0.5%). The study concluded that the most common treatment was ampicillin inj + gentamicin inj (54.7), with the most frequent DRPs being overdose (27.8%), the duration of treatment is too short (22.9%), infrequent dose regimen (18.8%), adverse drug incidence (16.9%), and underdose (10.1%).